Studies on Waqf Intention in Reputable Publication - Uula, Mimma Maripatul (International Journal of Waqf, 2024)
This study aims to examine the development of research on the topic of "Waqf Intention" and research plans that can be carried out based on journals published on this theme. This study uses a qualitative method with a bibliometric analysis approach. The data used is secondary data on the theme of "Waqf Intention" from the Scopus database, with a total of 51 journal articles. The data was then processed and analyzed using the VosViewer application to determine the bibliometric map of the development of "Waqf Intention" research in the world. The results of the study found that there were 5 clusters with the most frequently used words being intention, waqf, model, waqf institution, theory, knowledge, cash waqf, factor, and trust. Then, the research topics related to Waqf Intention were Behavioral intention toward waqf crowdfunding, Determinants of cash waqf intention, Knowledge level and waqf intention, Adoption of waqf accounting standards, and Waqf support for SME development.